Navigating The Future: Cutting-Edge Strategies For English Language Education In College - Delfia Herwanis (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The objective of this project is to investigate innovative strategies and approaches that can significantly revolutionize the process of learning the English language for current college students. The aim is to identify and analyze innovative teaching approaches that are in line with the learning preferences of modern students. The goal is to offer practical insights and guidance to educators who wish to implement creative teaching methods for English. The study's theoretical framework is built upon several key concepts and frameworks that provide a solid basis for understanding new approaches to English language education in higher education. The research findings, incorporating both quantitative and qualitative data, unequivocally confirm the positive impact of new teaching methods on student engagement, contentment, and perceived effectiveness. The findings of this study underscore the significance of using innovative approaches in English language teaching at the university level.